DISCOURSE-ORIENTED TRANSLATION STRATEGIES AND CULTURAL COMMUNICATIVE ADAPTATION - Uraimshikova Maftuna Rustam qizi (Modern American Journals, 2026)
This article examines discourse-oriented translation strategies with particular emphasis on cultural and communicative adaptation. The study argues that successful translation depends not only on linguistic equivalence but also on pragmatic, functional, and cultural correspondence. Drawing on translation strategy theories proposed by Venuti, Krings, Lörscher and Jääskeläinen, the paper analyzes how discourse context influences translation choices. Examples from dialogic discourse and phraseological units illustrate the application of pragmatic adaptation, functional equivalence, and compensation strategies. The findings highlight the translator’s role as a cultural mediator who ensures communicative effectiveness across languages.
Keywords: Discourse, translation strategies, cultural adaptation, communicative equivalence, pragmatics